2009
DOI: 10.1021/jf901207w
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes in Serum Pectins during Industrial Tomato Paste Production

Abstract: It is well-known that an irreversible decrease in serum viscosity occurs when tomato juice is concentrated by evaporation into paste. Several studies have suggested that the loss in serum viscosity is due to pectin depolymerization, caused by the high temperatures used during industrial tomato paste production. This study demonstrates that conformational changes in pectin may play a more important role than pectin depolymerization in the irreversible loss of serum viscosity during industrial tomato paste produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The low pH value of tomato‐derived products may hamper the β‐eliminative pectin solubilization and degradation (Keijbets and Pilnik ; Kravtchenko and others ; Krall and McFeeters ). Furthermore, chemical pectin demethoxylation and conformational changes can occur during thermal processing at high temperatures (De Roeck and others ; Diaz and others ).…”
Section: Structure Of Plant‐tissue‐based Food Suspensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low pH value of tomato‐derived products may hamper the β‐eliminative pectin solubilization and degradation (Keijbets and Pilnik ; Kravtchenko and others ; Krall and McFeeters ). Furthermore, chemical pectin demethoxylation and conformational changes can occur during thermal processing at high temperatures (De Roeck and others ; Diaz and others ).…”
Section: Structure Of Plant‐tissue‐based Food Suspensionsmentioning
confidence: 99%
“…So far, the literature describes a broad variety of procedures to examine the serum characteristics, in particular pectin composition. Whereas the pectin concentration is often determined by colorimetric measurements of the GalA content, the pectin molar mass is generally analyzed by high‐performance size‐exclusion chromatography equipped with a multiangle laser light scatter detector (Diaz and others ; Moelants and others ). The DM can be calculated as the ratio of the molar amount of methoxyl esters to the molar amount of GalA and can be measured colorimetrically, through infrared spectroscopy, and other methods (Lima and others ; Moelants and others ).…”
Section: Structure Of Plant‐tissue‐based Food Suspensionsmentioning
confidence: 99%
“…The trend in serum viscosity correlates well with the production of methanol ( R 2 = 0.98; data not shown), which reinforces the hypothesis that enzymatic depolymerization and solubilization of pectin molecules is causing a decrease in the consistency at the higher temperatures used in this study. However, loss of serum viscosity at the higher temperatures may also be due in part to conformational changes in the pectin molecules caused by thermal treatments rather than enzymatic depolymerization …”
Section: Resultsmentioning
confidence: 99%
“…However, loss of serum viscosity at the higher temperatures may also be due in part to conformational changes in the pectin molecules caused by thermal treatments rather than enzymatic depolymerization. 28 Per cent total solids, soluble solids and insoluble solids were not significantly affected by pre-treatment temperature (P >0.05) (data not shown). Other studies have shown that Bostwick value is directly correlated with solids content.…”
Section: Temperature Dependence Studymentioning
confidence: 88%
“…One type of commercially available pectin forms a gel after thermal treatment at 95˚C (203˚F), followed by cooling [10]. The high temperature facilitates a dissociated, disordered pectin conformation that facilitates the extraction process [11]. Similarly, hemicelluloses respond to high temperature in the same manner [12].…”
Section: Introductionmentioning
confidence: 99%